(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article discusses approaches to the development and adoption of managerial decisions in emergency situations that may be encountered by heads of state bodies and departments in the exercise of their official powers; the criteria and stages of making and implementing management decisions are also considered.